The Analysis of Education System in Uzbekistan: Challenges, Solutions and Statistical Analysis - Khamroyevna, Khaydarova Laylo (European Journal of Life Safety and Stability (2660-9630), 2021)
The article discusses new ways to develop the education system in Uzbekistan. At the same time, there is information about the need to use new ways to reform and develop the education system.